Long non-coding RNA-mediated competing endogenous RNA regulatory network during flower development and color formation in Melastoma candidum - Li, Hui; Wang, Wei; Liu, Rui; Tong, Botong; Dai, Xinren; Lu, Yan; Yu, Yixun; Dai, Seping; Ruan, Lin (Frontiers in Plant Science, 2023)
M. candidum, an evergreen shrubby flower known for its superior adaptation ability in South China, has gained increased attention in garden applications. However, scant attention has been paid to its flower development and color formation process at the non-coding RNA level. To fill this gap, we conducted a comprehensive analysis based on long non-coding RNA sequencing (lncRNA-seq), RNA-seq, small RNA sequencing (sRNA-seq), and widely targeted metabolome detection of three different flower developmental stages of M. candidum. After differentially expressed lncRNAs (DElncRNAs), differentially expressed mRNAs (DEmRNAs), differentially expressed microRNAs (DEmiRNAs), and differentially synthesized metabolites (DSmets) analyses between the different flower developmental stages, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were conducted to identify some key genes and metabolites in flavonoid, flavone, anthocyanin, carotenoid, and alkaloid-related GO terms and biosynthetic pathways. Three direct-acting models, including antisense-acting, cis-acting, and trans-acting between lncRNAs and mRNAs, were detected to illustrate the direct function of lncRNAs on target genes during flower development and color formation. Based on the competitive endogenous RNA (ceRNA) regulatory theory, we constructed a lncRNA-mediated regulatory network composed of DElncRNAs, DEmiRNAs, DEmRNAs, and DSmets to elucidate the indirect role of lncRNAs in the flower development and color formation of M. candidum. By utilizing correlation analyses between DERNAs and DSmets within the ceRNA regulatory network, alongside verification trials of the ceRNA regulatory mechanism, the study successfully illustrated the significance of lncRNAs in flower development and color formation process. This research provides a foundation for improving and regulating flower color at the lncRNA level in M. candidum, and sheds light on the potential applications of non-coding RNA in studies of flower development.